Pests and Diseases of Tropical Crops, volume 2: Field Handbook - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1990)
by D.J. Hill and J.M. Waller, 1988, 432pp, ISBN 0 582 606 152 price UKL9.95, available from Longmans Tropical Agriculture Series - Longman House - Burnt Mill - Harlow - Essex CM202JE- UK This book be used as a textbook by students and by...